Sosialisasi Kebijakan Penanaman Modal di Kabupaten Aceh Barat Daya - Alfian Anas; Cut Mega Putri; Tio Devilishanti; Mutiara Shifa; Rimal Mahdani (Jurnal Pengabdian Agro and Marine Industry, 2023)
The aim of this community service is to provide local business people with the knowledge they need to invest in Indonesia. The most recent investment-related laws and regulations are also covered in this activity. This activity provides explanations on a variety of investment-related topics as well as the most recent data on how simple it is to invest in Indonesia. This is crucial for improving investor comprehension so that they can always operate and grow their businesses in accordance with the most recent rules established by the Indonesian government. This includes understanding the rights that investors can obtain as well as the responsibilities that investors must fulfill when operating a business in Indonesia. The goal of this activity is also to help business actors submit LKPM (Investment Activity Reports) by online submission and to help business investors in the Southwest Aceh District understand the Investment Policy for conducting business and the implementation of the current Investment Policy.